High-dose-rate brachytherapy using molds for lip and oral cavity tumors - Unetsubo, Teruhisa (Radiat Oncol, 2015)
BACKGROUND: High-dose-rate (HDR) brachytherapy using the mold technique is a less invasive treatment for early lip and oral cavity cancer. However, limited reports exist regarding the feasibility of this method. In this retrospective study, we evaluated the outcome of this therapy and investigated its feasibility for lip and oral cavity tumors. METHODS: Between May 2002 and December 2010, 17 patients (median age, 80.0 years) with histologically confirmed squamous cell carcinoma of the lip or oral cavity were treated by means of HDR brachytherapy using the mold technique after external beam radiotherapy (EBRT). Tumor sites included the buccal mucosa in eight cases, the gingiva in three cases, the lips in two cases, the floor of the mouth in two cases, and the hard palate in two cases. For all patients, EBRT (30 Gy/15 fractions), was performed before HDR brachytherapy. Two 6-Gy fractions were delivered twice daily for 2 days a week with an interval of 6 hours between the fractions. The total HDR brachytherapy dose was 24 Gy. Prior to EBRT, two patients with neck metastasis underwent neck dissection, and one patient with an exophytic tumor underwent tumor resection. RESULTS: The median follow-up period was 53.4 (range, 4.8–83.4) months. Of the 17 patients, 14 (82.4%) achieved a complete response, and three (17.6%) displayed a partial response. The overall 3- and 5-year survival rates were both 68.8%, the 3- and 5-year disease-specific survival rates were both 86.7%, and the 3- and 5-year local control rates were both 54.1%. Seven patients developed local recurrence at a median time of 3.4 (range, 1.7–29.1) months after treatment. Nodal and lung metastases occurred separately in two patients. By the end of the follow-up period, two patients had died of the primary disease and four patients had died of other causes. CONCLUSIONS: Although there is a need to improve the technical aspects of the treatment protocol, HDR brachytherapy using the mold technique might be a therapeutic option for superficial lip or oral cavity tumors, especially in older patients who have a poor performance status or are in poor physical condition.